Chromium Removal from Tannery Effluent by Microbial Biomass - Sharma, Indu (My University, 2010)
In the present study bacterial isolates and consortium isolated from tannery effluent (CT) and chrome sludge (CS) were analyzed for Cr(VI) reduction. Molecular identification based on 16S rDNA sequence analysis led to the characterization of isolates as Raoultella sp. (CT4) and Citrobacter sp. (CT5) from tannery effluent and Bacillus cereus (CS7) and Citrobacter freundii (CS8) from chrome sludge. Studies revealed that the bacterial isolate Raoultella sp. (CT4) completely transformed Cr(VI) to Cr(III) whereas Bacillus cereus (CS7), Citrobacter freundii (CS8) and Citrobacter sp. (CT5) showed 94.81%, 95.8% and 95.2% of reduction respectively. Since biowastes from industrial fermentation units can serve as an economical and constant supply of biomass for biosorption of metal ions therefore two types of microbial biomass, which are generated as a byproduct of pharmaceutical fermentation industry involving fermentative production of certain antibiotics by Aspergillus sp. (MB1) and Streptomyces sp. (MB2) were collected from Ranbaxy (fermentation industry) Paonta Sahib, Himachal Pradesh, India and were characterized for physical and chemical parameter such as, pH, moisture, ash content, bulk density, CHN analysis and calorific value. Removal of Cr(III) from aqueous solution and tannery effluent was carried out using microbial biomass (MB1 and MB2) and various parameters including adsorbent dosage (0.25-2%), pH (2-6) and chromium concentration (5-50 mg/L) and contact time were standardized in batch mode and to investigate the mechanism of metal uptake by Fourier transform infrared (FTIR) and X-ray diffraction (XRD) analysis was done. Fourier transform infrared studies with microbial waste biomass revealed the involvement of C=N, C=C, C-H and C-O functional groups in chromium binding. Langmuir and Freundlich adsorption isotherms were predicted from the equilibrium sorption data. Correlation coefficient (r2) values indicate that the adsorption pattern for heavy metals followed both the Langmuir (r2 > 0.988) and Freundlich (r2 > 0.993) isotherms. A comparison of kinetic models applied to the biomass such as Lagergren, Ho and McKay, Elovich and Morris-Weber kinetic models indicates that adsorption of Cr(III) on microbial biomass follows a best Ho and McKay pseudo second-order rate equation and correlation coefficient (r2) correlated with the experimental data. Removal of Cr(III) from aqueous solution and tannery effluent by microbial biomass (MB1 and MB2) led to the development of a cost effective and eco-friendly process for removal of chromium from tannery effluent without generating toxic chemical sludge having industrial application. Maximum chromium removal capacity of microbial biomass Aspergillus sp. (MB1) and Streptomyces sp. (MB2) was 99.6 and 70.9% from tannery effluent in column mode. The high efficiency of the biosorption and elution, low biomass damage and stability over a prolonged operation time makes the new biosorption process an effective alternative for chromium pollution control.
Keywords: Chromium; tannery; bacteria; microbial biomass; FTIR; Kinetic models